Novel indazolylchromones: synthesis, fungicidal evaluation, molecular docking and aquatic toxicity prediction - Kundu, Riya; Shakil, Najam Akhtar; Narayanan, Neethu; Kamil, Deeba; Rana, Virendra Singh; Tripathi, Kailash P.; Kaushik, Parshant (Frontiers in Chemistry, 2024)
Fungal diseases cause substantial loss to agricultural crops, affecting both quantities and quality. Although several methods are used for preventing disease incidence, fungicides remain crucial for higher yields and better quality. But in the past, the efficacy of several fungicides has decreased due to increased cases of fungicide resistant. In our pursuit of new effective fungicides, we synthesised a series of twenty 2-Indazol-1-yl-chromen-4-one derivatives (6a- 6t). The characterization of synthesized compounds was performed by several spectroscopic methods including Infrared, Nuclear Magnetic Resonance (1H and 13C) and HRMS. Out of 20 synthesised compounds, 19 (6b- 6t) were found to be novel. All synthesised indazolylchromones showed very good antifungal activity against Sclerotium rolfsii and Fusarium oxysporum. Among the tested compounds, 6t and 6f exhibited very good fungicidal activity against S. rolfsii with an ED50 of 10.10 mg L-1 and 16.18 mg L-1, respectively. In case of Fusarium oxysporum compound 6f displayed good’ activity with an ED50 value of 27.82 mg L-1. Molecular docking study was done to predict the binding sites of most active compounds, 6t and 6f with Cytochrome P450 14alpha -sterol demethylase (CYP51) enzyme using molsoft software. The acute toxicity predictions the of synthesized compounds for fish (LC50,96 Hr), daphnid (LC50, 48 Hr) and green algae (EC50, 96Hr) and the chronic toxicity predictions (ChV) were assessed using Ecological Structure Activity Relationship (ECOSAR) model. As per ECOSAR prediction, all the chemicals are inside AD and not missing predictions.